UJI COBA PENANGKAPAN PADA RUMPON PORTABLE DI PERAIRAN PALABUHANRATU - Roza Yusfiandayani; Indra Jaya; Mulyono S. Baskoro (Jurnal Teknologi Perikanan dan Kelautan, 2013)
Fish Aggregating Device (FAD) usually used by small scale and large scale fishermen in Indonesia are FAD shallow and deep sea water which fix in the water. Efectivities and eficiency research activity about portable FAD in the water to catch thunnus spp. and skipjack have never been done in Indonesia. Need the research about portable FAD to catch thunnus spp. and skipjack in the water. This research can strong National Inovation System with portable FAD to help the fishermen in fishing operation methods. Catching trial around portable FAD by using experimental fishing used troll lines and hand lines. The purpose of this research are to know the number and composition of fish around portable FAD and to know stomacthcontent and plankton in the water.